(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Frequent occurrence of flash flood is an issue of concern in Nigeria which requires prompt attention. The global worming which triggers the climate change phenomenon is believed to be one of the major causes of flooding. This study reviewed several research works conducted on flood incidences in Nigeria, particularly the Hadejia river valley watershed. The updated and more recent literatures were visited, analyzed and discussed. It was found that for the last decades, there is increasing frequency of flash flood incidences in the study catchment which resulted into displacement of the inhabitants, loss of lives and properties. Substantial portion of the affected places were occupied by people which have been given flood alert and warning previous by climate scientists. Such awareness focused the preparedness and possible relocation in the event of flash flood occurrence. In conclusion, this study has disclosed that there is evidence of increasing rate of flood occurrence at Hadejia river valley catchment. Thus, more effort should be intensified on creating awareness and public enlightenment on how to mitigate the potential damage and loss of life and properties.